1999
DOI: 10.1023/a:1009887306055
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The electrical impedance properties of healthy and infarcted left ventricular myocardium differ markedly. The properties of the infarction border zone are intermediate between healthy and infarcted myocardium. Impedance may be a useful assay of cardiac tissue content and adaptable for cardiac mapping in vivo. Condensed Abstract. To delineate the electrical impedance properties of healthy and chronically infarcted left ventricular myocardium emphasizing the infarction border zone, impedance was measured in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…A capacitor cell consisting of two parallel square electrodes (each of 1.5 cm 2 surface area) with variable distance between them [26] was custom built to measure bulk electrical impedance of each sample using alternating-current (AC) impedance spectroscopy (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…A capacitor cell consisting of two parallel square electrodes (each of 1.5 cm 2 surface area) with variable distance between them [26] was custom built to measure bulk electrical impedance of each sample using alternating-current (AC) impedance spectroscopy (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…This notion is supported by the fact that a pacing stimulus in scarred myocardium leads to a prolonged and fragmented QRS complex [91,92] as well as electrical and mechanical dyssynchrony. Furthermore, it is known that myocardial scars are not readily excitable [93] and that they effectively reduce the volume of myocardium available to a LV pacing stimulus [94].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in sheep showed the 200% increase in myocardial impedance after 4 h of permanent coronary occlusion that turned to a 60% decrease 1 week later, and this was maintained 6 weeks after (Fallert et al, 1993). The mechanisms implicated in the progressive reduction of tissue resistivity during infarct healing are likely related to the sequential occurrence of interstitial edema, loss of myocyte content, and collagen and fat deposition in the ischemic region (Fallert et al, 1993; Schwartzman et al, 1999; Del Rio et al, 2008; Farraha et al, 2014). These structural derangements will be less marked in infarction areas with surviving myocardial cells and therefore could be detected by bioimpedance techniques.…”
Section: Discussionmentioning
confidence: 99%
“…These structural derangements will be less marked in infarction areas with surviving myocardial cells and therefore could be detected by bioimpedance techniques. In 4 sheep with 60-days old anterior myocardial infarction induced by permanent ligature of the LAD coronary artery, epicardial impedance measured with the 4-electrode technique at 1 kHz was lower in the visually defined dense infarction than in the border zone or in the healthy myocardium (Schwartzman et al, 1999). Using a 3 h LAD occlusion-reperfusion model in three sheep it has been reported that areas with greater myocardial injury (<50% viability), assessed by histologic examination, had greatest attenuation of impedance magnitude compared with areas with >50% viability in a 5 weeks-myocardial infarction (Farraha et al, 2014).…”
Section: Discussionmentioning
confidence: 99%